2017
DOI: 10.1136/bmjopen-2017-016904
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of a single group prospective observational study on the diagnostic value of 3T susceptibility weighted MRI of nigrosome-1 in patients with parkinsonian symptoms: the N3iPD study (nigrosomalironimagingin Parkinson’s disease)

Abstract: IntroductionParkinson’s disease (PD) is the most common movement disorder in the elderly and is characterised clinically by bradykinesia, tremor and rigidity. Diagnosing Parkinson’s can be difficult especially in the early stages. High-resolution nigrosome MRI offers promising diagnostic accuracy of patients with established clinical symptoms; however, it is unclear whether this may help to establish the diagnosis in the early stages of PD, when there is diagnostic uncertainty. In this scenario, a single photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…This study was conducted to assess the potential of using a simple and practical method of multiecho SWI ave in the delineation of the swallow-tail sign of nigrosome-1 and compare with the single-echo SWI which is the most commonly used in routine clinical practice [2,17]. The major findings of this study are: first, compared with the conventional single-echo SWI, the simple method using multiecho SWI ave can improve the CNR of the swallow-tail sign; second, significant correlations between neuromelanin signal and CNRs in QSM and T2 mapping, and T1 value of the nigrosome-1 were identified; third, the older subjects exhibited increased CNR values compared with the young adults.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to assess the potential of using a simple and practical method of multiecho SWI ave in the delineation of the swallow-tail sign of nigrosome-1 and compare with the single-echo SWI which is the most commonly used in routine clinical practice [2,17]. The major findings of this study are: first, compared with the conventional single-echo SWI, the simple method using multiecho SWI ave can improve the CNR of the swallow-tail sign; second, significant correlations between neuromelanin signal and CNRs in QSM and T2 mapping, and T1 value of the nigrosome-1 were identified; third, the older subjects exhibited increased CNR values compared with the young adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are required to demonstrate if this technique can be equivalent to DAT-SPECT. 14 The lack of standardization of imaging protocols including spatial resolution and imaging planes may limit its use 15 as well as the relative low sensitivity of MRI compared with nuclear imaging techniques such as PET or SPECT, although 3 T MRI avoids the risks associated with ionizing radiation. 16 The correlation between DNH abnormality and nigrostriatal dopaminergic dysfunction was analyzed in a few studies, as in a study of PD carriers of the G2019S, Leucine-rich repeat kinase 2 (LRRK2) mutation, in whom the loss of DNH predicted the ipsilateral striatal DAT signal abnormality with a sensitivity of 87.5% and a specificity of 83.6%.…”
Section: High-field Mri Dorsal Nigral Hyperintensitymentioning
confidence: 99%
“…Usually, nigrosome-1 is not detected in patients with PD, i.e., there is no hyperintense signal in the corresponding area of SN. It is suggested that the absence of nigrosome-1 visualization in PD may be associated not only with the loss of dopaminergic neurons but also with the simultaneous process of significant iron accumulation [51][52][53]. The sensitivity of this technique in differentiating PD from the normal and non-degenerative parkinsonism approaches 100%, and the specificity in these cases is 87-100% [52,[54][55][56].…”
Section: Instrumental Testsmentioning
confidence: 99%
“…Used for differentiating PD patients from healthy subjects, but not able to differentiate from some cases of atypical parkinsonism (MSA, PSP, and CBD) [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Clinical Testsmentioning
confidence: 99%